Modeling C540-C20 fullerene collisions - Rysaeva, Leysan Kh. (2019)
Collisions of C20 and C540 fullerenes are studied in a wide range of velocities by means of classical molecular dynamics. The simulations show that the collision scenario strongly depends on the collision velocity of the fullerenes. At low collision energies, the fullerenes are repelled by the van der Waals forces, and after bouncing off a part of the kinetic energy of their translational motion is converted into the energy of cage vibrations. At higher collision energies, the fullerenes overcome the potential barrier of Pauli repulsion with the formation of the new chemical bonds, and a significant change in the geometry of the molecules is observed. At very high collision energies, structure of the molecules is destroyed with the formation of new carbon clusters. Analysis of collisions for fullerenes of significantly different size revealed some new features associated with their asymmetric energy exchange.